Idle-Time Garbage-Collection Scheduling. - DEGENBAEV, ULAN; EISINGER, JOCHEN; ERNST, MANFRED; MCILROY, ROSS; PAYER, HANNES (Communications of the ACM, 2016)
The article provides information on an approach used by the programming language JavaScript engine V8 in the Chrome internet browser to schedule garbage-collection pauses when Chrome is idle. It details how this approach can reduce user-visable dropped frames, or jank, on real-world websites and result in fewer dropped frames and memory consumption.